Analysis of Factors Inhibiting Science Learning in the Implementation of the Kurikulum Merdeka in the High Schools in Palembang - Noviyanti, Deby; Pebriyanti, Risa; Pangestu, Ikhsan; Hidayat, Saleh; Saputri, Wulandari; Astriani, Meli (Universitas PGRI Semarang, 2023)
Education is an important sector in the development of a country. The progress of a nation is very dependent on the education system. To improve the quality of learning, many countries, including Indonesia, have adopted new curriculum, such as the Kurikulum Merdeka. The Kurikulum Merdeka gives students freedom in their learning and emphasizes the development of 21st-century skills. However, the application of this curriculum is faced with several inhibiting factors. This study aims to analyze the inhibiting factors in implementing the Kurikulum Merdeka at SMA Muhammadiyah 6 and SMA Aisyiyah 1 Palembang. This study uses a qualitative approach with data collection techniques in the form of interviews and information surveys. The results showed that the internal inhibiting factors for implementing the Kurikulum Merdeka came from the motivation, attitudes, and interests of the students. In addition, external inhibiting factors also come from parental support, principal leadership, school facilities, learning systems, learning materials, and teacher competence. It can be concluded that there are obstacles in all the indicators measured. With a deep understanding of these inhibiting factors, it is hoped that it can provide recommendations for the authorities and become a reference for schools in efforts to correct deficiencies and develop the Kurikulum Merdeka in the future.